Validation of the Czech Version of the Dysphagia in Multiple Sclerosis Questionnaire (DYMUS) - Novotná, Klára; Motýl, Jiří; Friedová, Lucie; Menkyová, Ingrid; Andělová, Michaela; Vodehnalová, Karolína; Lízrova-Preiningerová, Jana; Uher, Tomáš; Horáková, Dana (Dysphagia, 2023)
Dysphagia is a common symptom of neurological disease, including multiple sclerosis (MS). The DYsphagia in MUltiple Sclerosis (DYMUS) questionnaire was developed as a screening tool for swallowing problems. The purpose of the present study was to validate the Czech version of the DYMUS questionnaire. We validated the questionnaire on a sample of 435 patients with MS and 135 healthy controls (HC) chosen by accidental sampling from larger, long-term studies conducted by the Prague MS Center. For the purposes of this study, we used both electronic (primary method of distribution) and paper-based (backup) versions of the questionnaire. The internal consistency of the whole scale was satisfactory (Cronbach's α =0.833). The DYMUS mean score in HC was 0.215 (standard deviation [SD] = 0.776). Normative data suggested a cut-off value for dysphagia between 1 and 2 points. Principal component analysis (PCA) showed a two-factor structure of the adapted scale. However, the structure did not completely correspond to the originally proposed dimensions of dysphagia for solids and liquids; our data supported dropout of item Q10. Criterion validity was proved by the difference in dysphagia between HC and patients MS (U = 25,546, p < 0.001) and by a positive correlation with the EDSS (Kendall's tau-b = 0.169, p < 0.001) and other patient-reported outcomes. The Czech version of the DYMUS questionnaire is a valid and reliable tool for evaluating swallowing impairment in Czech-speaking patients with MS. Moreover, the questionnaire can be administered electronically, with a paper-based backup.
Keywords: Czech Republic; Patient Reported Outcome Measures; průzkumy a dotazníky; roztroušená skleróza; Česká republika; Reproducibility of Results; lidé; reprodukovatelnost výsledků; Deglutition Disorders; Humans; Surveys and Questionnaires; Multiple Sclerosis; hodnocení výsledků péče pacientem; poruchy polykání